Sportfisheries, conservation and sustainable livelihoods: a multidisciplinary guide to developing best practice. Issue 3 (30th December 2015) - Barnett, Adam; Abrantes, Kátya G; Baker, Ronald; Diedrich, Amy S; Farr, Marina; Kuilboer, Alf; Mahony, Tracey; McLeod, Ian; Moscardo, Gianna; Prideaux, Murray; Stoeckl, Natalie; van Luyn, Ariella; et al.
Abstract: Ecotourism ventures in developing countries are often among the few alternatives for enhancing sustainable livelihoods without altering traditional ways of life. The best way forward is to continually develop and implement best practice guidelines and, in particular, to flexibly develop them to suit individual cases. We conduct a multidisciplinary assessment of best practice guidelines required to develop and sustain sportfishing tourism in developing countries, while enhancing local livelihoods and promoting environmental stewardship. In general, best practice guidelines should be developed around a sustainable livelihood framework that includes short‐term coping mechanisms and longer‐term capacity building. Sportfishing development that conforms to ecological and socially orientated criteria, founded on site‐specific research that captures local environmental and social complexities, has the potential to provide mutual benefits to tourists and local people, fuelling community development and enhancing the cultural experience of tourists. Best practice guidelines for sportfishing that do not address these dimensions are unlikely to result in a viable industry. Given the current interest and growth of sportfishing in developing countries, the proposed guidelines can help a range of end users manage, conserve and maximize livelihood benefits from their fishery.